In Praise of Jus Cogens’ Conceptual Incoherence - Ohlin, Jens (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2018)
The most compelling account of jus cogens is that it flows from natural law and constitutes the “ethically minimum” content of international law. Although natural law was once considered an acceptable and obvious approach to jurisprudence, its significance has waned at the expense of legal positivism. However, the hierarchical quality of jus cogens is best explained by some element of natural law—and its explicit invocation of moral content—rather than anything one might find in legal positivism. Of course, international lawyers have persistently refused to recognize the latent naturalism within jus cogens. While rueful from the point of view of legal theory, the obfuscation was nonetheless essential for jus cogens to succeed. In an alternate world where jus cogens was correctly viewed as a vestige of natural law, modern international lawyers would never have accepted it. One might lament the failure to recognize the natural law origins of jus cogens because it hampered the development of standards for identifying which legal norms counted as jus cogens. However, no account of jus cogens offers compelling, unambiguous criteria, and second, the lack of clarity on its criteria was a good price to pay in exchange for the legal category’s widespread adoption. In the end, the notion that jus cogens is consistent with international law’s legal positivism was a useful fiction, a “noble lie” that gave us modern human rights law.